Influencia de la lactancia materna en el desarrollo psicomotor en la primera infancia. Centro Infantil Elisa Mariño .Octubre 2024-enero 2025 - Patín Patín, Nelson Ramiro (2025)
The present study aimed to determine the influence of breastfeeding techniques on the psychomotor development of children aged 12 to 36 months who attended the Elisa Mariño Children's Center from October 2024 to January 2025. The research was conducted using a quantitative, correlational approach, a non-experimental, and cross-sectional design. The population consisted of 60 children, and the LATCH scale was used as an instrument to evaluate the quality of breastfeeding and the Denver Test II to measure psychomotor development. The results revealed that most children were exclusively breastfed during the first six months, which was significantly related to adequate psychomotor development, particularly in the areas of gross motor skills, fine motor skills, and language. In contrast, those who received mixed or bottle feeding reported a higher number of failed tests on the Denver Test, as well as reports of growth problems. Based on the findings, a promotional strategy was designed with educational activities aimed at mothers and caregivers, with the goal of promoting exclusive breastfeeding as a protective factor for child development. The conclusion is that strengthening breastfeeding education can have a positive impact on children's health and psychomotor development.